On the collision of two elastic solids with plane boundaries - Burenin, Anatoliy Aleksandrovich; Dudko, Olga Vladimirovna; Potianikhin, Dmitriy Andreevich (Computational Continuum Mechanics, 2013)
The self-similar problem of the collision of two nonlinearly elastic solids with plane nonparallel boundaries is considered. The mechanical properties of colliding solids are characterized by different sets of elastic constants. It is shown that, depending on the friction coefficient, both slip and adhesion between the surfaces in contact may occur. The choice of a unique solution out of mathematically possible solutions is governed by the second law of thermodynamics and the shockwave evolutionary condition. The solution of this problem is carried out as a series of computational experiments involving simultaneous verification of wave pattern selection criteria.
Keywords: theory of elasticity; shock wave; Riemann waves; computational experiment